Catalytic slurry oil hydrodesulfurization catalyst and preparation method thereof

By using catalysts prepared by large pore phthalite and pore reamer, the problem of excessive sulfur content and insufficient reaction of colloidal and asphaltene in the production of needle coke raw materials is solved, efficient sulfur removal and aromatic retention are achieved, and the quality of needle coke raw materials is improved.

CN119909705AActive Publication Date: 2025-05-02PETROCHINA CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202311432015.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

The prior art is difficult to effectively use medium and high sulfur catalytic oil slurry to produce high-quality needle-shaped coke raw materials, resulting in excessive sulfur content and insufficient reaction of colloids and asphaltene, affecting the quality of the electrode.

Method used

Large-porous slurry as support, isosorbide and polystyrene as pore reamers, combined with acid metal impregnation liquid and amino acid complexing agent, a catalyst with suitable pore size and high pore volume was prepared for catalyzing the hydrodesulfurization reaction of oil slurry.

Benefits of technology

It achieves efficient sulfur removal and asphaltene conversion, maintains the content of tricyclic and tetracyclic aromatic hydrocarbons, and improves the quality of needle-shaped coke raw materials and the stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a catalytic slurry oil hydrodesulfurization catalyst and a preparation method thereof, and the preparation method comprises the following steps: adding an extrusion aid and a pore-enlarging agent into macroporous pseudo-boehmite, mixing, adding an acidic metal impregnation liquid, kneading, forming, drying and roasting to obtain the catalyst, the extrusion aid is prepared from isosorbide and polystyrene. The method is simple in process and low in cost, and the prepared catalyst has proper pore size, high desulfurization effect and asphaltene conversion capacity, and well retains tricyclic and tetracyclic aromatic hydrocarbons.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a catalytic oil slurry hydrodesulfurization catalyst and a preparation method thereof. Background Art

[0002] Ultra-high power graphite electrodes use needle coke as raw material and are used in electric arc furnace steelmaking, which can reduce carbon emissions by 60% compared with blast furnace steelmaking. The Ministry of Industry and Information Technology has clearly proposed to "encourage the promotion of short-process steelmaking technology and equipment using scrap steel as raw materials." The increase in the proportion of short-process steelmaking is expected to further increase the demand for upstream key material graphite electrodes. High-quality needle coke is the key raw material for ultra-high power graphite electrodes.

[0003] As a rich by-product of catalytic cracking (FCC), catalytic cracking oil contains a large amount of 2-5 ring aromatic hydrocarbons, which are almost all short side chain aromatic hydrocarbons after catalytic cracking reaction. Low sulfur catalytic oil can be used as an excellent raw material for producing needle coke. However, at present, there is a shortage of low sulfur high quality slurry suitable for producing needle coke, and it is necessary to make full use of medium and high sulfur slurry. However, medium and high sulfur slurry contains a large amount of heteroatoms such as sulfur, nitrogen, oxygen and asphaltene heavy components. When the sulfur content of needle coke is high (>0.8wt%), it will be violently released during the graphitization process, resulting in irreversible volume expansion, causing the formation of microcracks and reducing the quality of the electrode. The sulfur content of oil-based needle coke raw materials is <0.5wt%, ash content ≤100mg / kg, asphaltene ≤2wt%, and aromatic content 35-50wt%. Therefore, it is necessary to make full use of the existing medium and high sulfur catalytic oil slurry and carry out hydrogenation pretreatment. In terms of raw material pretreatment, it mainly involves oil slurry desolidification and slurry refining process. Filtration + furfural extraction or supercritical extraction to adjust the oil slurry components. In the aspect of oil slurry refining, a lot of research has been conducted both at home and abroad. The main process is hydrofining to reduce the content of impurities such as sulfur and nitrogen in oil slurry. For the selective hydrodesulfurization reaction of oil slurry, the performance of the catalyst is the key. Among them, the pore structure of the catalyst carrier (specific surface area, pore volume and pore size distribution) not only has an important influence on the dispersion of the active components, but also directly related to the diffusion and mass transfer during the reaction process. The pore size and pore type will affect the internal diffusion rate of the reactants and products. Most of the metal and sulfur impurities in oil slurry exist in colloids and asphaltene, which are the components with the largest molecular weight and the most complex structure in the oil slurry components. The diffusion resistance is large and the pores are prone to blockage (causing the catalyst to deactivate). Therefore, the pore volume of the catalyst is particularly important. A large pore volume is required to facilitate the passage of large molecules containing impurities and react inside the catalyst pores, while maintaining a large specific surface is conducive to the desulfurization activity. Although catalytic cracking oil slurry is a by-product of catalytic cracking reaction, the molecular size becomes smaller, and the side chains of oil slurry molecules become shorter and the steric hindrance effect of the side chains becomes smaller, it is still necessary to increase the content of 15-20nm and 20-30nm pores in a targeted manner to promote the adsorption and desorption reaction of large molecular sulfides and asphaltene molecules into the catalyst pores for conversion.

[0004] CN101724420A discloses a method for producing needle coke raw materials by processing catalytic cracking slurry and conventional coking raw materials using a delayed coking process. In this method, the slurry is fed from the middle and upper part of the coke tower, and the conventional coking raw materials are fed from the bottom of the coke tower. In the coke tower, the slurry contacts with high-temperature oil and gas, removes components that are not conducive to the production of needle coke, and obtains coking wax oil as a needle coke raw material through the side line of the coking fractionation tower. However, in this method, since the slurry does not pass through the radiation section of the heating furnace, the temperature is relatively low and the slurry is all fed from the middle and upper part, the residence time is relatively short, which makes some colloids and asphaltene unable to fully react, and will be carried into the coking wax oil by the oil and gas, thereby affecting the quality of the obtained needle coke raw material; moreover, if the sulfur content in the catalytic cracking slurry is high, the sulfur content in the obtained coking wax oil is difficult to meet the requirements, so the application of this method is quite limited.

[0005] CN1872963A discloses a raw material pretreatment method for producing needle coke, wherein the raw material oil is first subjected to vacuum distillation to remove non-ideal components, the remaining ideal components are contacted with hydrogen and a hydrogenation catalyst, and the hydrogenation reaction stream is separated to obtain the raw material for producing needle coke. This method requires a separate filtering and vacuum distillation device, which requires a large investment, and the needle coke raw material obtained by this method still contains a certain amount of colloid and asphaltene, which will affect the quality of the needle coke, and it is difficult to produce high-grade needle coke products.

[0006] CN103013567B introduces a method for producing needle coke raw materials from catalytic cracking oil slurry. In this patent, a protection zone and a hydrogenation reaction zone are set. The catalytic oil slurry first enters the protection zone to absorb most of the catalyst powder, and then is mixed with hydrogen and enters the heating furnace. After heating, it enters the hydrogenation reaction zone for hydrogenation treatment reaction. The protection zone is filled with an adsorbent that can absorb catalyst powder, and the hydrogenation reaction zone is filled with a protective agent, a demetallizing agent and a desulfurizing agent. Due to the presence of catalyst powder, the protection zone needs to be frequently switched, which increases the operation and management costs of the device; secondly, in order to remove sulfur from the catalytic oil slurry, a fixed bed hydrogenation reactor is set for hydrogenation desulfurization. Since the catalytic oil slurry contains a large amount of unsaturated hydrocarbons, these unsaturated hydrocarbons are easily polymerized in the fixed bed hydrogenation reactor to block the catalyst bed, which leads to an increase in the bed pressure drop and a shortened device operation cycle.

[0007] CN108102711B provides a combined process for producing needle coke, wherein the raw oil enters a catalytic cracking device, the catalytic oil slurry obtained after reaction separation is mixed with hydrogen and then enters an ebullated bed reactor, the liquid product heavy component obtained after separation of the reaction effluent of the ebullated bed reactor enters a coking device, the oil and gas generated by the coking reaction are separated to obtain gas, coking gasoline, coking diesel and coking wax oil, and the needle coke generated after the reaction cycle is completed is deposited in the coking device. In the method of the present invention, the catalytic section of the ebullated bed reactor is filled with a hydroprocessing catalyst, and the specific surface area of ​​the special catalyst in the present invention is 120m 2 / g~300m 2 / g, preferably 160m 2 / g~280m 2 / g; pore volume is 0.2mL / g~0.8mL / g, preferably 0.4mL / g~0.6mL / g; average pore diameter is 8nm~13nm, preferably 9nm~11nm and the following pore size distribution: the volume of pores with diameters of 4nm~10nm accounts for 70%~80% of the total pore volume, and the volume of pores with diameters of 15nm accounts for 5%~10% of the total pore volume. The process of this invention is complicated, and the pore volume and diameter of the catalyst used are small, which is not conducive to the diffusion of macromolecules such as asphaltene, and the required hydrogenation process conditions are relatively harsh. Although sulfur impurities in the catalytic oil slurry can be removed, aromatics are lost.

[0008] CN114984970A The present invention provides a grading method and application of a desolidified catalytic oil slurry hydrodesulfurization catalyst, the grading method comprising: when the sulfur content of the desolidified catalytic oil slurry is ≥0.8%, and the content of three-ring and four-ring aromatic hydrocarbons is ≥55%, the reactor is sequentially loaded with a selective dearomatization catalyst, a direct desulfurization catalyst and a hydrodesulfurization catalyst from top to bottom; when the sulfur content of the desolidified catalytic oil slurry is 0.35-0.8%, and the content of three-ring and four-ring aromatic hydrocarbons is 40-55%, the reactor is sequentially loaded with a direct desulfurization catalyst and a hydrodesulfurization catalyst from top to bottom. The grading method of the present invention achieves efficient desulfurization while retaining as many three-ring and four-ring aromatic hydrocarbons in the desolidified catalytic oil slurry as possible, and the desolidified catalytic oil slurry is subjected to a hydrodesulfurization reaction to obtain a high-quality needle coke raw material.

[0009] The invention of CN112342059A provides a method for blending catalytic cracking oil slurry with a delayed coking device. The catalytic cracking oil slurry enters a hydroprocessing unit. The hydroprocessing unit is provided with a hydrogenation reaction zone and a gas-liquid separation zone. The hydrogenation reaction zone is sequentially loaded with a hydrogenation protective agent, a hydrodemetallization agent and / or a hydrodesulfurization agent along the direction of the logistics, and the particle size of the catalyst loaded at the end of the hydrodemetallization agent or the hydrodesulfurization agent along the direction of the logistics is not less than 1.6 mm. The catalytic cracking oil slurry contacts with the catalyst in the hydroprocessing zone in the presence of hydrogen-containing gas to react. The reaction effluent enters the gas-liquid separation zone for separation to obtain hydrogen-rich gas and liquid phase flow. The liquid phase flow enters the delayed coking device together with the delayed coking raw material for reaction. After separation, the reaction effluent obtains coking dry gas, liquefied gas, coking gasoline, coking diesel, coking wax oil and coke.

[0010] CN106622314A discloses a high-activity hydrorefining catalyst and a preparation method thereof, wherein water is used as a solvent to prepare a slurry containing silicon-phosphorus-alumina, a boron-containing compound, a VIB group metal compound and a VIII group metal compound are added to the slurry, a filter cake and a filtrate are obtained by filtration, the filtrate is mixed with SB powder and a peptizing agent to obtain an adhesive, and the adhesive and the filter cake are successively rolled, formed, dried and calcined to obtain the hydrorefining catalyst. The catalyst has a small pore volume and a fast deactivation rate.

[0011] CN1053458C discloses a residual oil hydroprocessing catalyst and a preparation method thereof, which uses γ-Al2O3 as a carrier and supports metal elements of Group VIII and Group VIB, and is characterized in that the catalyst has a pore volume of 0.30-0.60 mL / g, a specific surface area of ​​120-200 m2 / g, an average pore diameter of 9.0-13.0 nm, and the ratio of pore volume with a pore diameter of 7.0-13.0 nm to the total pore volume is greater than 80%. The catalyst prepared by the method has a large specific surface area, a small macropore ratio, poor resistance to metal poisoning, and rapid deactivation.

[0012] CN1417300A discloses a hydrogenation catalyst and its preparation method. The preparation method of the catalyst comprises impregnating a macroporous alumina carrier with a solution containing metal compounds of Group VIB and Group VIII. The preparation method of the alumina carrier comprises extruding a mixture of pseudo-boehmite, acid, water and an extrusion aid into a molded product. The molded product is quickly dried within 35 minutes at 90-300°C and calcined at 600-800°C in a steam-containing atmosphere for at least 0.5 hours. The pore distribution of the obtained alumina carrier is such that pores with a diameter of 10-20nm account for 70-90% of the total pore volume.

[0013] CN1103009A discloses a method for preparing a heavy oil hydrodemetallization catalyst carrier, which is prepared by mixing two aluminum hydroxide precursors with different pore size distributions, adding carbon black and surfactant as pore-enlarging agents, and forming a double-pore alumina carrier through kneading, drying and calcining. This method has strict requirements on the precursor alumina raw material, requires the addition of more surfactants, and has a high cost. Summary of the invention

[0014] The object of the present invention is to provide a catalytic oil slurry hydrodesulfurization catalyst and a preparation method thereof. The method has a simple process and low cost. The prepared catalyst has a suitable pore size, has a high desulfurization effect and asphaltene conversion ability, and better retains three-ring and four-ring aromatic hydrocarbons.

[0015] To achieve the above-mentioned purpose, the present invention provides a method for preparing a catalytic oil slurry hydrodesulfurization catalyst, comprising the following steps: adding an extrusion aid and a pore expanding agent to macroporous pseudo-boehmite for mixing, then adding an acidic metal impregnation solution, kneading, molding, drying and roasting to obtain a catalyst; the pore expanding agent comprises isosorbide and polystyrene.

[0016] The preparation method of the catalytic oil slurry hydrodesulfurization catalyst of the present invention comprises the following steps: the isosorbide is added in an amount of 0.5wt% to 6wt% of the alumina content in the pseudo-boehmite, preferably 2% to 4%; the polystyrene is added in an amount of 2wt% to 8wt% of the alumina content in the pseudo-boehmite, preferably 4wt% to 6wt%.

[0017] The method for preparing the catalytic oil slurry hydrodesulfurization catalyst of the present invention, wherein the specific surface area of ​​the macroporous pseudo-boehmite is ≥330m 2 / g, pore volume ≥1.15ml / g.

[0018] The method for preparing a catalytic oil slurry hydrodesulfurization catalyst of the present invention comprises an active metal precursor, an inorganic acid and a complexing agent in the acidic metal impregnation liquid.

[0019] In the preparation method of the catalytic oil slurry hydrodesulfurization catalyst of the present invention, the complexing agent is an amino acid substance, and the added amount is 1wt% to 15wt% of the pseudo-boehmite, preferably 3wt% to 10wt%.

[0020] In the method for preparing a catalytic oil slurry hydrodesulfurization catalyst of the present invention, the complexing agent is one or more of arginine, histidine and lysine.

[0021] The preparation method of the catalytic oil slurry hydrodesulfurization catalyst of the present invention, the active metal in the acidic metal impregnation liquid is a metal of Group VIB and / or Group VIII as a hydrogenation active metal component, preferably the active metal is at least one of Mo and W and at least one of Ni and Co. The precursor of the Mo element is one or more of ammonium molybdate, sodium phosphomolybdate, and ammonium phosphomolybdate; the precursor of the W element is ammonium tungstate, tungsten nitrate, and ammonium metatungstate; the precursor of the Ni element is one or more of nickel nitrate, nickel acetate, and basic nickel carbonate; the precursor of the Co element is one or more of cobalt nitrate, basic nickel cobalt carbonate, and cobalt naphthenate. In terms of oxides, molybdenum and / or tungsten account for 8wt% to 20wt% of the total mass of the catalyst, and nickel and / or cobalt account for 2wt% to 5wt% of the total mass of the catalyst.

[0022] In the method for preparing a catalytic oil slurry hydrodesulfurization catalyst of the present invention, the inorganic acid is one or more of phosphoric acid, nitric acid and hydrochloric acid, and the amount of the inorganic acid is not particularly limited. The function of the inorganic acid is to dissolve the active metal precursor, and those skilled in the art can adjust it according to actual conditions.

[0023] The preparation method of the catalytic oil slurry hydrodesulfurization catalyst of the present invention, the extrusion aid is a cellulose material, the addition amount is 1wt% to 6wt% of the alumina content in the pseudo-boehmite, preferably 2 to 4wt%, the cellulose material is a commonly used material in the field, specifically methyl cellulose, ethyl cellulose, hydroxymethyl cellulose, the present invention does not make special limitations.

[0024] The preparation method of the catalytic oil slurry hydrodesulfurization catalyst of the present invention adopts a screw extruder in the molding process, and its extrusion pressure is 15-50Mpa. The shape of the catalyst can be changed as needed, such as cylindrical, three-leaf clover, four-leaf clover and spherical; the drying temperature of the drying process is 100-200°C.

[0025] In the method for preparing the catalytic oil slurry hydrodesulfurization catalyst of the present invention, the calcination temperature is 500-900° C., preferably 680-850° C., and the calcination time is 0.5-6 hours.

[0026] To achieve the above purpose, the present invention also provides a catalyst prepared by the method, with a pore volume of 0.60-0.95 ml / g, pores of 15nm-20nm accounting for 40%-60% of the total pore volume, and pores of 20-30nm accounting for 20%-30% of the total pore volume.

[0027] Beneficial effects of the present invention:

[0028] The method provided by the present invention first uses macroporous pseudo-boehmite, adds isosorbide and polystyrene, physically expands the polystyrene to expand the pores of 15-20nm, and the hydroxyl groups in isosorbide are combined with the hydroxyl groups in the macroporous pseudo-boehmite, and the isomeric carbon chains expand the pores of 20-30nm. The increase in the macropore ratio helps asphaltene and colloid macromolecules to react and transform inside the catalyst pores, thereby improving the desulfurization rate; the addition of an amino acid complexing agent improves the dispersion and acidity of the metal salt and retains tricyclic and tetracyclic aromatic hydrocarbons.

[0029] The catalyst prepared by the method provided by the present invention has a higher desulfurization effect and asphaltene conversion ability, and better retains tricyclic and tetracyclic aromatic hydrocarbons. DETAILED DESCRIPTION

[0030] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.

[0031] Example 1

[0032] Weigh 500g of pseudo-boehmite dry glue powder (specific surface area 330m 2 / g, pore volume 1.18ml / g), add 3.5g methyl cellulose (1wt%), 1.8g isosorbide (0.5wt%) and 7g polystyrene (2wt%), mix well; add 500ml Mo-Ni-P solution (the catalyst contains MoO3 10wt%, NiO 5wt%) and knead, wherein the configuration of Mo-Ni-H3PO4 solution is as follows: add 50g molybdenum trioxide to 100ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir to dissolve completely, add 15g arginine and stir to dissolve completely, add water to make up to 500ml; then extrude into a four-leaf clover shape with a particle size of 1.4-1.6mm on a front extrusion single screw extruder, extrusion pressure 15MPa, dry at 100℃ for 3 hours, calcined at 700℃ for 6 hours, and obtain catalyst A1. Catalyst properties are shown in Table 1.

[0033] Example 2

[0034] Weigh 500g of pseudo-boehmite dry glue powder (specific surface area 330m 2 / g, pore volume 1.18ml / g), add 3.5g methyl cellulose (1wt%), 20g isosorbide (6wt%) and 28g polystyrene (8wt%), mix well; add 500ml Mo-Ni-P solution (the catalyst contains MoO3 10wt%, NiO 5wt%) and knead, wherein the configuration of Mo-Ni-H3PO4 solution is as follows: add 50g molybdenum trioxide to 100ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir to dissolve completely, add 45g histidine and stir to dissolve completely, add water to make up to 500ml; then extrude into a clover shape with a particle size of 1.6mm on a front extrusion single screw extruder, extrusion pressure 40MPa, dry at 200℃ for 3 hours, and then calcine at 900℃ for 3 hours to obtain catalyst A2. Catalyst properties are shown in Table 1.

[0035] Example 3

[0036] Weigh 500g of pseudo-boehmite dry glue powder (specific surface area 330m 2 / g, pore volume 1.18ml / g), add 20g methyl cellulose (6wt%), 20g isosorbide (6wt%) and 10g polystyrene (3wt%), mix well; add 500ml Mo-Ni-P solution (the catalyst contains MoO3 10wt%, NiO 5wt%) and knead, wherein the configuration of Mo-Ni-H3PO4 solution is as follows: add 50g molybdenum trioxide to 100ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir to dissolve completely, add 45g lysine and stir to dissolve completely, add water to make up to 500ml; then extrude into a cylindrical shape with a diameter of 1.6mm on a front extrusion single screw extruder, extrusion pressure 25MPa, dry at 120℃ for 3 hours, and then roast at 500℃ for 6 hours to obtain catalyst A3. Catalyst properties are shown in Table 1.

[0037] Example 4

[0038] Weigh 500g of pseudo-boehmite dry glue powder (specific surface area 330m 2 / g, pore volume 1.18ml / g), add 10g methyl cellulose (3wt%), 10g isosorbide (3wt%) and 28g polystyrene (8wt%), mix well; add 500ml Mo-Ni-P solution (the catalyst contains MoO310wt%, NiO 5wt%) and knead, wherein the Mo-Ni-H3PO4 solution is configured as follows: add 50g molybdenum trioxide to 200ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir until completely dissolved, add 50g serine, add water to make up to 500ml; then extrude into a clover shape with a diameter of 1.6mm on a front extrusion single screw extruder, dry at 120℃ for 3 hours, and then roast at 850℃ for 5 hours to obtain catalyst A4. Catalyst properties are shown in Table 1.

[0039] Example 5

[0040] Weigh 500g of pseudo-boehmite dry glue powder (specific surface area 330m 2 / g, pore volume 1.18ml / g), add 10g methyl cellulose (3wt%), 10g isosorbide (3wt%) and 10g polystyrene (3wt%), mix well; add 500ml Mo-Ni-P solution (the catalyst contains MoO3 10wt%, NiO 5wt%) and knead, wherein the Mo-Ni-H3PO4 solution is configured as follows: add 50g molybdenum trioxide to 200ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir until completely dissolved, add 75g arginine, add water to make up to 500ml; then extrude into a clover shape with a diameter of 1.6mm on a front extrusion single screw extruder, extrusion pressure 15MPa, dry at 120℃ for 3 hours, and then roast at 900℃ for 0.5 hours to obtain catalyst A5. Catalyst properties are shown in Table 1.

[0041] Example 6

[0042] Weigh 500g of pseudo-boehmite dry glue powder (specific surface area 330m 2 / g, pore volume 1.18ml / g), add 10g methyl cellulose (3wt%), 20g isosorbide (6wt%) and 10g polystyrene (3wt%), mix well; add 500ml Mo-Ni-P solution (the catalyst contains MoO3 10wt%, NiO 5wt%) and knead, wherein the configuration of Mo-Ni-H3PO4 solution is as follows: add 50g molybdenum trioxide to 200ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir until completely dissolved, add 15g lysine, add water to make up to 500ml; then extrude into a cylindrical shape with a diameter of 1.6mm on a front extrusion single screw extruder, extrusion pressure 25MPa, dry at 120℃ for 3 hours, and then roast at 800℃ for 5 hours to obtain catalyst A6. Catalyst properties are shown in Table 1.

[0043] Comparative Example 1

[0044] According to the method described in Chinese patent CN106622314A, 25g of molybdenum trioxide and 16g of basic nickel carbonate were added to the slurry containing silicon-phosphorus-alumina, filtered to obtain a filter cake and a filtrate, the filtrate was mixed with SB powder and a peptizing agent to obtain an adhesive, the adhesive and the filter cake were extruded into a clover shape with a diameter of 1.6mm on a front extrusion single screw extruder, dried at 120°C for 3 hours, and then calcined at 800°C for 5 hours to obtain catalyst B1. The catalyst properties are shown in Table 1.

[0045] Comparative Example 2

[0046] According to the method described in Chinese patent CN1053458C, 500g of pseudo-boehmite dry rubber powder was taken, 80g of ammonia solution (containing 3% ammonia solution) was added, and kneading was carried out for 30min. 240g of acetic acid acidic aqueous solution was added, and kneading was carried out for 40min. The mixture was extruded and calcined at 800°C to prepare a carrier. 150ml of Mo-Ni-P solution (containing MoO3 10wt%, NiO 5wt%) was added for impregnation, wherein the Mo-Ni-H3PO4 solution was prepared as follows: 25g of molybdenum trioxide was added to 100ml of H3PO4 solution and stirred to dissolve completely, 16g of basic nickel carbonate was added and stirred until completely dissolved, and water was added to make up to 150ml; after the spraying was completed, the excess solution was filtered off, the mixture was dried at 120°C for 3 hours, and then calcined at 500°C for 4 hours to obtain catalyst B2.

[0047] Comparative Example 3

[0048] According to the method described in Chinese patent CN1417300A, 300g of pseudo-boehmite was weighed, mixed evenly with 3.9g of 65wt% nitric acid, 3g of sesbania powder and 120g of deionized water, and extruded into a 1.6mm clover shape on an extruder. The mixture was dried by forced air at 110°C. After drying, 100% water vapor was introduced into the dried molded product at 750°C and calcined for 5 hours to obtain a carrier. 150ml of Mo-Ni-P solution (containing 10wt% MoO3 and 3.5wt% NiO) was added to the obtained product for impregnation, wherein the Mo-Ni-H3PO4 solution was prepared as follows: 25g of molybdenum trioxide was added to 100ml of H3PO4 solution and stirred to dissolve completely, then 16g of basic nickel carbonate was added and stirred until completely dissolved, and then water was added to make up to 150ml. After spray impregnation, the excess solution was filtered off, dried at 120°C for 3 hours, and then calcined at 500°C for 4 hours to obtain catalyst B3.

[0049] Comparative Example 4

[0050] Weigh 500g of pseudo-boehmite dry glue powder (specific surface area 330m 2 / g, pore volume 1.18ml / g), add 3.5g methyl cellulose (1wt%), 2g sorbitol (0.5wt%) and 7g polystyrene (2wt%), mix well; add 500ml Mo-Ni-P solution (the catalyst contains MoO3 10wt%, NiO 5wt%) and knead, wherein the configuration of Mo-Ni-H3PO4 solution is as follows: add 50g molybdenum trioxide to 100ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir to dissolve completely, add 15g arginine and stir to dissolve completely, add water to make up to 500ml; then extrude into a four-leaf clover shape with a particle size of 1.4-1.6mm on a front extrusion single screw extruder, extrusion pressure 15MPa, dry at 100℃ for 3 hours, calcined at 700℃ for 6 hours, and obtain catalyst B4. Catalyst properties are shown in Table 1.

[0051] Table 1 Catalyst properties

[0052]

[0053] The results in Table 1 show that, compared with the comparative example, the specific surface area and pore volume of the catalyst prepared by the method described in the embodiment of the present invention are greater than those of the comparative example, and the content of pores with pore diameters of 15-20 nm and 20-30 nm is significantly higher than that of the comparative example.

[0054] The activity stability of the catalyst in Table 1 was evaluated. The evaluation conditions are shown in Table 2, and the evaluation results are shown in Table 3.

[0055] Table 2 Catalyst evaluation conditions

[0056] Catalytic oil properties <![CDATA[Density (20 °C) / g·cm -3 > 1.078 Sulfur, wt% 0.8 Tricyclic + tetracyclic, wt% 47 Asphaltene, wt% 6.8 Process conditions Reaction temperature, °C 385 Hydrogen partial pressure, MPa 8 <![CDATA[Space velocity, h -1 > 0.8 Hydrogen / Oil Ratio 700

[0057] Table 3 Evaluation results

[0058] catalyst A1 A2 A3 A4 A5 A6 B1 B2 B3 B4 Sulfur content, wt% 0.39 0.34 0.38 0.36 0.37 0.35 0.40 0.39 0.41 0.41 Tricyclic+tetracyclic, wt% 46.2 47.3 46.0 46.3 45.8 46.4 41.5 42.3 41.9 44.5 Asphaltene, wt% 2.0 1.8 2.0 2.1 2.0 1.9 2.8 2.9 2.6 2.4

[0059] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a catalytic oil slurry hydrodesulfurization catalyst, characterized in that: The following steps are involved: An extrusion aid and a pore expanding agent are added to macroporous pseudo-boehmite for mixing, and then an acidic metal impregnation solution is added, kneaded, molded, dried and calcined to obtain a catalyst; the pore expanding agent includes isosorbide and polystyrene.

2. The method for preparing a catalytic slurry hydrodesulfurization catalyst according to claim 1, characterized in that: The amount of isosorbide added is 0.5wt% to 6wt% of the aluminum oxide content in the pseudo-boehmite; the amount of polystyrene added is 2wt% to 8wt% of the aluminum oxide content in the pseudo-boehmite.

3. The method for preparing a catalytic slurry hydrodesulfurization catalyst according to claim 1, characterized in that: The specific surface area of ​​the macroporous pseudo-boehmite is ≥330m 2 / g, pore volume ≥1.15ml / g.

4. The method for preparing a catalytic slurry hydrodesulfurization catalyst according to claim 1, characterized in that: The acidic metal impregnation solution comprises an active metal precursor, an inorganic acid and a complexing agent.

5. The method for preparing a catalytic slurry hydrodesulfurization catalyst according to claim 4, characterized in that: The complexing agent is an amino acid substance, and the added amount is 1wt% to 15wt% of the pseudo-boehmite.

6. The method for preparing a catalytic slurry hydrodesulfurization catalyst according to claim 5, characterized in that: The complexing agent is one or more of arginine, histidine and lysine.

7. The method for preparing a catalytic slurry hydrodesulfurization catalyst according to claim 4, characterized in that: The inorganic acid is one or more of phosphoric acid, nitric acid and hydrochloric acid.

8. The method for preparing a catalytic slurry hydrodesulfurization catalyst according to claim 4, characterized in that: The active metal is at least one of Mo and W and at least one of Ni and Co.

9. The method for preparing a catalytic slurry hydrodesulfurization catalyst according to claim 1, characterized in that: The extrusion aid is a cellulose substance, and the added amount is 1wt% to 6wt% of the alumina content in the pseudo-boehmite.

10. The method for preparing a catalytic slurry hydrodesulfurization catalyst according to claim 1, characterized in that: The calcination temperature is 500-900° C., and the calcination time is 0.5-6 hours.

11. A catalyst prepared by the method according to any one of claims 1 to 10, characterized in that: The pore volume is 0.60-0.95 ml / g, pores of 15 nm-20 nm account for 40%-60% of the total pore volume, and pores of 20-30 nm account for 20%-30% of the total pore volume.

Citation Information

Patent Citations

  • Production method of needle coke raw material

    CN101724420A

  • Method for preparing needle coke material by catalytic cracking slurry

    CN103013567B

  • Catalyzer for hydrotreating residuum and its prepn. method

    CN1053458C

  • High-activity hydrofining catalyst and preparation method thereof

    CN106622314A

  • A combined process for producing needle coke

    CN108102711B